How will e-scooter companies develop a competitive advantage? - Osland, Asbjr̜n (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Bird, Lime, and other electric scooter (e-scooter) providers have experienced a surge in popularity in U.S. cities. Bird claims to operate in more than 100 U.S. cities and Lime was at 101 cities on December 6, 2018 (see corporate websites). Scalability is important to investors. The e-scooters are convenient for riders in downtown areas or close to universities. Through the use of smartphones, riders rent the e-scooters and then leave them wherever they finish their ride. Future riders with the appropriate app can then locate them on their smartphones. Contractors or employees pick up the e-scooters at the end of the day, recharge them at night, and the next morning they place them in areas known to be popular for future riders. The major issues the companies faced were getting approval to operate in cities, not endangering pedestrians, and competing with other e-scooter companies. Since the e-scooters available from different firms are functionally equivalent and priced comparably, execution by the company is crucial. This includes maintenance of the e-scooters, daily distribution of the devices after overnight charging, and maintaining sound relationships with the city where the operation is located. Users tend to choose an e-scooter company based on availability at the needed location. Cities need to give the businesses permission to operate. It is clear that investors believe there is a need to change transportation systems in congested urban areas, given the large amounts invested in Bird, Lime, and other firms. Segway-Ninebot manufactures 90% of the e-scooters in China. Cities grant approval for specific numbers of e-scooters in their city. The students are asked to weigh in on what is the sustainable competitive advantage of one company relative to others.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bird -- (Firm); Lime -- (Firm); Lease and rental services -- Management -- Case studies; Scooters -- Transportation; Urban transportation